Clitoria ternatea blue petal extract protects against obesity, oxidative stress, and inflammation induced by a high-fat, high-fructose diet in C57BL/6 mice. (December 2022) - Wang, Yijun; Liu, Tiantian; Xie, Yanmei; Li, Na; Liu, Yan; Wen, Jiaqiang; Zhang, Man; Feng, Wanjie; Huang, Jinbao; Guo, Yuanxin; Kabbas Junior, Tufy; Wang, Dongxu; et al.
Graphical abstract: Highlights: Aqueous extract (AE) of butterfly pea petals has mainly flavonoids (anthocyanins). AE ameliorated the oxidative stress and inflammation mediators in obese mice. AE reduced plasma leptin, free fatty acid, LDL, and hepatic MDA contents. AE reduced total cholesterol and ameliorated insulin resistance in obese mice. AE exert hypolipidemic/anti-inflammatory effects by promoting reverse cholesterol transport. Abstract: This study examined the chemical compounds and bioactivity of the aqueous extract of Clitoria ternatea blue petals and investigated its beneficial effects in vivo on a mouse model of obesity and metabolic syndrome. The extract mainly contained flavonoids, and nine compounds were tentatively identified. Male C57BL/6J mice were either fed a standard diet (SD) or a high-fat, high-fructose diet (HFFD) for 16 weeks, and HFFD-fed animals were treated with 0.25%, 0.5%, and 2% (w/w) of the aqueous extract in drinking water. The aqueous extract ameliorated oxidative stress and inflammation mediators. Furthermore, the aqueous extract reduced plasma leptin, free fatty acid, low-density lipoprotein cholesterol levels and hepatic malondialdehyde content. The aqueous extract significantly reduced total cholesterol and ameliorated insulin resistance. The results demonstrated that the aqueous extract of C. ternatea blue petals contains bioactive anthocyanins that exert substantial hypolipidemic and anti-inflammatory effects by promoting reverse cholesterol transport in HFFD-fed mice.